Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Red clover RNA virus 1: functional analysis of ORF2 protein, associations with co-infecting viruses, and seed transmission - Ekaterina A. Lazareva; Alexander A. Lezzhov; Denis A. Chergintsev; Eugeny A. Tolstyko; Igor V. Selifonov; Anastasia K. Atabekova; Sergey Y. Morozov; Andrey G. Solovyev (Archives of Virology, 2026)

Ir-based oxygen evolution reaction catalysts: Role of microstructure and activation protocols - Margarita V. Kozlova; Elizaveta A. Moguchikh; Anastasia A. Alekseenko; Angelina S. Pavlets; Ilya V. Pankov; Egor E. Aydakov; Vasily V. Kaichev; Maksim A. Solovyev; Irina V. Pushkareva; Dmitri G. Bessarabov; Artem S. Pushkarev (Chemical Engineering Journal, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Hidden diversity of cestode Nippotaenia in a widely distributed invasive fish Perccottus glenii - Sergey G. Sokolov; Pavel G. Vlasenko; Misako Urabe; Dmitry M. Atopkin; Andrey N. Reshetnikov; Peimin Yang; Gelena V. Izotova; Marina B. Shedko; Mikhail M. Solovyev (Hydrobiologia, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Hi-C metagenomics facilitate comparative genome analysis of bacteria and yeast from spontaneous beer and cider - Ignat V. Sonets; Mikhail A. Solovyev; Valeriia A. Ivanova; Petr A. Vasiluev; Aleksey V. Kachalkin; Sofia D. Ochkalova; Anton I. Korobeynikov; Sergey V. Razin; Sergey V. Ulianov; Alexander V. Tyakht (Food Microbiology, 2024)

Description of a new species from 125 years old National Zoological Collections and three new records of family Limacodidae (Lepidoptera) from India - Jalil Ahmad; Navneet Singh; Alexey V. Solovyev; Rahul Joshi (International Journal of Tropical Insect Science, 2024)

Dependence of element composition of bile of freshwater and marine fishes on some abiotic and biotic factors - Mikhail M. Solovyev; Anastasiya V. Shokurova; Olesya V. Anishchenko; Pavel G. Vlasenko; Elena N. Kashinskaya; Karl B. Andree (Frontiers in Marine Science, 2023)
Introduction The elemental composition and physical properties of fish bile is a very important marker for ecotoxicological and physiological studies as bile is able to accumulate elements from environmental compartments. In the present study we focused on the effects of long term (seasons and years) and spatial distance (different water bodies) as well as other biotic (feeding habits, fish species, gut morphology) and abiotic (water salinity) factors on element composition of bile of 429 individuals belonging to 22 forms/species of fishes. Methods Element composition was determined using an inductively coupled plasma optical emission spectrometry. The fishes were analyzed from one marine (the Kandalaksha Gulf of the White Sea), two freshwater oligotrophic (Teletskoye and Baunt lakes), and one freshwater eutrophic water body (Chany Lake). In parallel, we have estimated the volume and density of bile from the same fishes using an automatic pipette and electronic balance. Results and discussion Based on fish bile density and volume data, we hypothesize that gastric fish species (those fishes that have a stomach) require a low volume of bile, but with higher density if compared to agastric fish species (those lacking a stomach) that mainly possessed large volumes of bile, but with a lower density. We have found that the concentrations of the following Na, K, Ca, Mg, S, P (major elements) and Al, Cu, Fe, Sr, Zn (trace elements) were the highest among the 28 elements studied. There were significant findings to contribute to a better understanding of the physiology of bile. First, we have determined the conditions formed in a water body in a given year (season) are more important for element composition of fish bile rather than other tested factors (feeding habits, gut morphology, etc.). Second, the feeding habits of fishes (carnivorous compared to non-carnivorous) had a significant effect based on differences among several elements. Third, the clear distinction between marine and freshwater fishes was found only for K and Na. Understanding which elements are produced as part of waste elimination and those that are present as a consequence of vital biological functions could improve the ecotoxicological study of bile as a marker of heavy metal contamination.

Estimating range disjunction time of the Palearctic Admirals (Limenitis L.) with COI and histone H1 genes - Vladimir I. Solovyev; Vladimir V. Dubatolov; Valeriya Y. Vavilova; Oleg E. Kosterin (Organisms Diversity & Evolution, 2022)

A common founder effect of the splice site variant c.-23 + 1G > A in GJB2 gene causing autosomal recessive deafness 1A (DFNB1A) in Eurasia - Aisen V. Solovyev; Alena Kushniarevich; Elena Bliznetz; Marita Bady-Khoo; Maria R. Lalayants; Tatiana G. Markova; Gabriel Minárik; L’udevít Kádasi; Ene Metspalu; Vera G. Pshennikova; Fedor M. Teryutin; Elza K. Khusnutdinova; et al. (Human Genetics, 2022)

Localization of the proteinase inhibitor activity in the fish cestode Eubothrium rugosum - Galina I. Izvekova; Tatyana V. Frolova; Evgeny I. Izvekov; Elena N. Kashinskaya; Mikhail M. Solovyev (Journal of Fish Diseases, 2021)
The mechanisms enabling fish tapeworms to avoid proteolytic attacks by digestive enzymes of their fish host have been studied in less detail compared with mammalian cestodes. This study aimed to assess the inhibitory ability towards trypsin and chymotrypsin in Eubothrium rugosum, an intestinal parasite of burbot Lota lota , and establish its localization in the tapeworm. To this end, the worms were treated with Triton X‐100 followed by differential centrifugation to isolate the tegumental brush border membrane. The protease inhibitory abilities of the worms were mostly determined by their excretory/secretory products released into the incubation medium. These inhibitory abilities proved to be linked mainly with the brush border fractions. Notably, the per cent inhibition of both studied digestive enzymes (trypsin and chymotrypsin) hardly depended on the duration of the parasite exposure in the incubation medium, probably due to intermittent glycocalyx renewal. Improved knowledge on functions of the excretory/secretory proteins produced by fish tapeworms may contribute to a better understanding of host–parasite relations and development of new approaches to the treatment and prevention of diseases caused by pathogenic helminths.

Conceptualization of the Construction of a Device for Measuring Forces and Torques during Neurosurgical Procedures - M. A. Solovyev; A. A. Vorotnikov; A. A. Grin; D. D. Klimov; Yu. V. Poduraev; V. V. Krylov (Biomedical Engineering, 2020)

Selective Heterozygous Advantage of Carriers of с.-23+1G>A Mutation in GJB2 Gene Causing Autosomal Recessive Deafness 1A - A. V. Solovyev; N. A. Barashkov; F. M. Teryutin; V. G. Pshennikova; G. P. Romanov; A. M. Rafailov; N. N. Sazonov; L. U. Dzhemileva; M. I. Tomsky; O. L. Posukh; E. K. Khusnutdinova; S. A. Fedorova (Bulletin of Experimental Biology and Medicine, 2019)

Ultrasound Treatment of Infected Wounds: Situation and Perspectives - D. A. Solovyev; S. I. Shchukin; S. P. Skvortsov; A. P. Nikolaev; P. V. Luzhnov (Biomedical Engineering, 2019)

Opinions of hearing parents about the causes of hearing impairment of their children with biallelic GJB2 mutations - Aisen V. Solovyev; Lilya U. Dzhemileva; Olga L. Posukh; Nikolay A. Barashkov; Marita S. Bady-Khoo; Semen L. Lobov; Natalya Yu. Popova; Georgii P. Romanov; Nikolay N. Sazonov; Alexander A. Bondar; Igor V. Morozov; Mikhail I. Tomsky; et al. (Journal of Community Genetics, 2017)

Plant-specific 4/1 polypeptide interacts with an endoplasmic reticulum protein related to human BAP31 - Anna V. Pankratenko; Anastasia K. Atabekova; Ekaterina A. Lazareva; Viktoriia E. Baksheeva; Oxana A. Zhironkina; Evgeni Yu Zernii; Robert A. Owens; Andrey G. Solovyev; Sergey Y. Morozov (Planta, 2017)

Range of a Palearctic uraniid moth Eversmannia exornata (Lepidoptera: Uraniidae: Epipleminae) was split in the Holocene, as evaluated using histone H1 and COI genes with reference to the Beringian disjunction in the genus Oreta (Lepidoptera: Drepanidae) - Vladimir I. Solovyev; Vera S. Bogdanova; Vladimir V. Dubatolov; Oleg E. Kosterin (Organisms Diversity & Evolution, 2015)

Feeding habits and ontogenic changes in digestive enzyme patterns in five freshwater teleosts - M. M. Solovyev; E. N. Kashinskaya; G. I. Izvekova; E. Gisbert; V. V. Glupov (Journal of Fish Biology, 2014)
Feeding habits and the activity of digestive enzymes (total alkaline proteases, α ‐amylase and lipase) from dace Leuciscus leuciscus , roach Rutilus rutilus , Prussian carp Carassius auratus gibelio , perch Perca fluviatilis and pikeperch Sander lucioperca fry were studied in the Malye Chany Lake–Kargat Estuary (western Siberia, Russia). The diet of fry from all studied species was mainly composed of chironomid larvae and zooplanktonic organisms ( i.e. cladocera and copepoda), whereas carnivorous species such as P. fluviatilis and S. lucioperca also preyed on fry from other fishes while detritus and microalgae were also important in the diet of ommivorous species. When comparing diet similarity (Sørensen–Dice index, Q S ) among fry at different stages of development, both omnivorous and carnivorous species showed a high level of similarity (0·67 Q S Q S α ‐amylase:total proteases (A:P) values higher than 1 in omnivorous species and lower (A:P ≤ 1) in carnivorous species.

Thiol Antioxidants in Combination with Vitamin B12 Induce Apoptotic Death of Human Lymphocytic Leukemia Cells by Destabilization of Lysosomes with the Involvement of Iron Ions - M. E. Solovyeva; A. A. Faskhutdinova; V. V. Solovyev; V. S. Akatov (Bulletin of Experimental Biology and Medicine, 2013)

Abundance of plastid DNA insertions in nuclear genomes of rice and Arabidopsis - Ilham A. Shahmuradov; Yagut Yu. Akbarova; Victor V. Solovyev; Jalal A. Aliyev (Plant Molecular Biology, 2003)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Analysis of mutation rates in the SMCY/SMCX genes shows that mammalian evolution is male driven - A. I. Agulnik; C. E. Bishop; J. L. Lerner; S. I. Agulnik; V. V. Solovyev (Mammalian Genome, 1997)